PERAN KEPALA MADRASAH DALAM PENGELOLAAN SARANA DAN PRASARANA PENDIDIKAN DI MTS NEGEI BALIGE - Hijriani Tambunan (Hijri, 2018)
This research aims to know the role of head of the madrasa in the management ofeducational facilities and infrastructure that consists of planning and infrastructure, the use of infrastructure, maintenance of facilities and infrastructure, surveillance means and infrastructures, and the coordination between the head of the madrasa with teachers about educational facilities and infrastructure in MTs Country Balige. This study uses qualitative methods. Information sources in this study is the head of the madrasa, Deputy Head of the madrasa, the Chief of staff, administrative staff and teachers. As for the data collection techniques used with observation, interview and documentation. Qualitative data analysis using data analysis models, Miles and Huberman with data reduction stages, presentation of data, conclusion and withdrawal. The results of this research show that: 1) Planning and infrastructure in the country, namely: Balige MTs a) Do menyususn plan and planning meeting in the procurement of infrastructure and facilities. 2) the use of facilities and infrastructure in the country is by Balige MTs makes the rule schedule in usage and infrastructure penddikan. 3) maintenance of facilities and infrastructure in MTs Country by involving all citizens of Balige madrasah in the care infrastructure and its storage form. 4) supervision of facilities and infrastructure in the country is by Balige MTs checked against reports and infrastructure and also checked directly against the facilities and infrastructure that is owned. 5) coordination between the head of the madrasa with the teacher yautu by conducting meetings on the management of the infrastructure and facilities and cooperate in achieving the purpose of the madrasa. Key words: The Role Of The Head Of The Madrasa, Educational Facilities And Infrastructure Management